2003
DOI: 10.1038/ncb989
|View full text |Cite
|
Sign up to set email alerts
|

MKP3 mediates the cellular response to FGF8 signalling in the vertebrate limb

Abstract: The mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) and phosphatidylinositol-3-OH kinase (PI3K)/Akt pathways are involved in the regulatory mechanisms of several cellular processes including proliferation, differentiation and apoptosis. Here we show that during chick, mouse and zebrafish limb/fin development, a known MAPK/ERK regulator, Mkp3, is induced in the mesenchyme by fibroblast growth factor 8 (FGF8) signalling, through the PI3K/Akt pathway. This correlates with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
232
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(247 citation statements)
references
References 40 publications
14
232
1
Order By: Relevance
“…Third, using phosphorylated-ERK as an indicator of FGF signal activation, it has been shown that only cells in the distal mesenchyme of the limb bud are under the influence of FGF (Corson et al, 2003). This is confirmed by the expression patterns of Spry genes and Mkp3, which are transcriptionally regulated by FGF signaling (Eblaghie et al, 2003;Kawakami et al, 2003;Minowada et al, 1999). Consistent with our hypothesis, the expression pattern of Spry4 complements the observed cell death domain in normal limb buds (compare Fig.…”
Section: Fgfr1 Expressed In Lbm Is Essential For Cell Survivalmentioning
confidence: 65%
See 1 more Smart Citation
“…Third, using phosphorylated-ERK as an indicator of FGF signal activation, it has been shown that only cells in the distal mesenchyme of the limb bud are under the influence of FGF (Corson et al, 2003). This is confirmed by the expression patterns of Spry genes and Mkp3, which are transcriptionally regulated by FGF signaling (Eblaghie et al, 2003;Kawakami et al, 2003;Minowada et al, 1999). Consistent with our hypothesis, the expression pattern of Spry4 complements the observed cell death domain in normal limb buds (compare Fig.…”
Section: Fgfr1 Expressed In Lbm Is Essential For Cell Survivalmentioning
confidence: 65%
“…1E,F). To assess the impact on FGF signal reception, we assayed for the expression of genes regulated by FGFs, including sprouty (Spry) 2, Spry4 and Mkp3 (Dusp6 -Mouse Genome Informatics) (Eblaghie et al, 2003;Kawakami et al, 2003;Minowada et al, 1999). Their expression suggests that FGF signaling is markedly reduced, although not abolished, in the Tcre;Fgfr1 limb buds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MKP-3 specifically binds to and inactivates ERK1 and 2, and recent studies indicate that this enzyme plays a pivotal role in regulating MAP kinase activity in response to fibroblast growth factor signaling during early development (6,41). MKPs exhibit distinct subcellular localization in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first clue as to a physiological function for DUSP6/MKP-3 came with the observation that it is expressed at many sites of fibroblast growth factor (FGF) signalling during early mouse development (Dickinson et al, 2002a). Subsequent studies in the developing limbs and nervous tissues in chicken embryos demonstrated that DUSP6/MKP-3 expression was mediated by FGFs as a component of a negative feedback control to regulate levels of activated ERK MAPK in these tissues (Eblaghie et al, 2003;Kawakami et al, 2003). There is currently some confusion as to which of the intracellular signalling pathways that lie downstream of the FGF-receptor is responsible for mediating DUSP6/MKP-3 expression, with evidence supporting a role for either ERK MAPK or PI3-kinase signalling in this process (Eblaghie et al, 2003;Kawakami et al, 2003;Tsang et al, 2004;Gomez et al, 2005;Smith et al, 2005).…”
Section: Mkps and The Regulation Of Immune Functionmentioning
confidence: 99%